Antibacterial Property of Different Medicinal Plants: Ocimum sanctum, Cinnamomum zeylanicum, Xanthoxylum armatum and Origanum majorana - Joshi, Bishnu; Lekhak, Sunil; Sharma, Anuja (Kathmandu University Journal of Science, Engineering and Technology, 2010)
Countries like Nepal and India have been using crude plants as medicine since Vedic period. A major part of the total population in developing countries still uses traditional folk medicine obtained from plant resources (Farnsworth 1994). With an estimation of WHO that as many as 80% of worlds population living in rural areas rely on herbal traditional medicines as their primary health care, the study on properties and uses of medicinal plants are getting growing interests. In recent years this interest to evaluate plants possessing antibacterial activity for various diseases is growing (Clark and Hufford, 1993). Based on local use of common diseases and Ethnobotanical knowledge, an attempt has been made to assess the antibacterial properties of selected medicinal plants.VIZ. Ocimum sanctum (Tulsi), Origanum majorana (Ram Tulsi), Cinnamomum zeylanicum (Dalchini), and Xanthoxylum armatum (Timur), for potential antibacterial activity against 10 medically important bacterial strains, namely Bacillus subtilis, Bacillus cereus, Bacillus thuringiensis, Staphylococcus aureus, Pseudomonas spp, Proteus spp, Salmonella Typhi, Escherichia coli, Shigella dysentriae, Klebsiella pneumoniae. The antibacterial activity of ethanol extracts was determined by agar well diffusion method. The plant extracts were more active against Gram-positive bacteria than against Gram-negative bacteria. The most susceptible bacteria were B. subtilis, followed by S. aureus, while the most resistant bacteria were E.coli, followed by Shigella dysenteriae, Klebsiella pneumoniae and Salmonella typhi. From the screening experiment, Origanum majorana showed the best antibacterial activity; hence this plant can be further subjected to isolation of the therapeutic antimicrobials and pharmacological evaluation. The largest zone of inhibition was obtained with Xanthoxylum armatum against Bacillus subtilis (23mm) and the minimum bactericidal concentration (MBC) value of 2.5 mg/l was obtained. Key words: Antibacterial property; Gram positive bacteria; Gram negative bacteria; zone of inhibition; minimum bactericidal concentration DOI: 10.3126/kuset.v5i1.2854 Kathmandu University Journal of Science, Engineering and Technology Vol.5, No.1, January 2009, pp 143-150